Attachment security and HPA axis reactivity to positive and challenging emotional situations in child-mother dyads in naturalistic settings - Roque, Lisa (2012)
This study investigated adrenocortical activity in response to different challenging and positive affect emotional contexts in child–mother dyads, as function of attachment security (children’s secure base behaviors and mothers’ attachment representations). Fifty-one children ranging in age from 18 to 26 months and their mothers participated in this study. Secure children showed significant increases in their cortisol levels after fear episodes and significant decreases, after positive affect ones. No significant changes were found for frustration/ anger episodes. Insecure children did not show significant differences in cortisol levels in any of the episodes, which suggests that insecure attachment may be related to hypothalamic–pituitary–adrenal axis suppression in response to challenging and positive contexts. Mothers of insecure children showed significantly higher cortisol concentrations in pre- and post-session samples, than mothers of secure children. Mothers’ personal attachment representations influenced their own cortisol responses, as well as their children’s (in a marginal significant way).